Political communication as a tool to strengthen customary law at indigenous village in Bali - Suputra, I Gede Mas (Bali Tourism Board, 2024)
Bali is renowned for its cultural diversity and unique local wisdom, particularly within the context of Hindu traditions. Balinese customary law is a foundation that plays a crucial role in preserving cultural values, maintaining traditions, and conserving the local wisdom that defines the island. However, political communication can also be considered both a scientific activity and a political activity within the political system. In general terms, political communication is a communication process that contains political messages. In political communication, messages conveyed by communicators or communicatees do not necessarily need large-scale or deeply political messages. In the context of globalization, Bali, as part of Indonesia, faces challenges in maintaining its cultural identity, especially within the framework of customary law. Balinese customary law is critical in preserving cultural values, Hindu traditions, and local wisdom. Although customary law is private, the state's recognition and protection of the Balinese customary law community are increasingly realized through the amendments to the 1945 Constitution and the ratification of Law No. 11 of 2005. In the political context, implementing Balinese customary law involves political communication strategies, including community education, media engagement, collaboration between legal and customary institutions, shared language, dialogue, and community participation. The standard principles in Balinese customary law emphasize shared understanding when facing differences, and effective political communication is necessary to ensure the sustainable and fair enforcement of customary law.